Screening for hepatocellular carcinoma - Koza, Jarosław; Orłowski, Krzysztof; Jurgoński, Adam; Meder, Agnieszka; Pujanek, Małgorzata; Ameryk, Monika; Kwiatkowska, Renata; Świątkowski, Maciej (Journal of Education, Health and Sport, 2017)
Introduction and purpose of the work. Hepatocellular carcinoma (HCC) is one of the most common malignant tumours all over the world. It is considered to be the sixth malignant tumour in terms of incidence. It is also characterized by high mortality rate, which, depending on the geographic region, gives the second or third place on the list of cancer related death. There are many known risk factors for the development of hepatocellular carcinoma, the most important of which is liver cirrhosis. Thus the cirrhotic patients are generally accepted for screening. Actually it is recommended to perform abdominal ultrasound every 6 months in this group. Other forms of screening are also tested. Description of the current knowledge and conclusions. Literature review provides indisputable evidences for the need of screening for liver cancer. Doubts remain only about the appropriateness of widening the screening group and possibly extending the scope of diagnostic tools. The authors, by analyzing the available knowledge for hepatocellular carcinoma screening, consider the qualification of actually recommended screening tests to be insufficient in countries with high incidence. Relatively high incidence of HCC, even greater mortality in the context of all cancers, safety, low cost and universal access to ultrasound, should, in the opinion of the authors, be enough for the consideration to widen the screening guidelines in countries with high incidence of HCC. In countries with low incidence, e.g. in Poland, the screening in healthy population do not belong to the priority.